2015
DOI: 10.1016/j.febslet.2015.04.029
|View full text |Cite
|
Sign up to set email alerts
|

Differential regulation of Connexin50 and Connexin46 by PI3K signaling

Abstract: Gap junction channels can modify their activity in response to cell signaling pathways. Here, we demonstrate that Cx50 coupling, but not Cx46, increased when co-expressed with a constitutively active p110α subunit of PI3K in Xenopus oocytes. In addition, inhibition of PI3K signaling by blocking p110α, or Akt, significantly decreased gap junctional conductance in Cx50 transfected HeLa cells, with no effect on Cx46. Alterations in coupling levels were not a result of Cx50 unitary conductance, suggesting that cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 45 publications
0
16
0
Order By: Relevance
“… 35 , 38 , 39 , 46 Interestingly, Cx50 has the greatest level of functional activity in epithelial cells in the early postnatal period when lens mitosis switches to the pulsatile growth pattern, and Cx50 conductance can be upregulated by p110α activity. 39 , 47 Thus, one possibility is the absence of p110α results in a delay in the upregulation of Cx50 gap junction channels in epithelial cells at P0, producing a transient decrease in germinative zone proliferation. The availability of a lens-specific p110α knockout mouse model will allow future testing of this hypothesis through interbreeding with Cx50-deficient mice to test for functional epistasis.…”
Section: Discussionmentioning
confidence: 99%
“… 35 , 38 , 39 , 46 Interestingly, Cx50 has the greatest level of functional activity in epithelial cells in the early postnatal period when lens mitosis switches to the pulsatile growth pattern, and Cx50 conductance can be upregulated by p110α activity. 39 , 47 Thus, one possibility is the absence of p110α results in a delay in the upregulation of Cx50 gap junction channels in epithelial cells at P0, producing a transient decrease in germinative zone proliferation. The availability of a lens-specific p110α knockout mouse model will allow future testing of this hypothesis through interbreeding with Cx50-deficient mice to test for functional epistasis.…”
Section: Discussionmentioning
confidence: 99%
“…This phosphorylation site might therefore act as a molecular switch to increase GJIC under these conditions [ 44 ]. A potential regulation of Cx50 but not Cx46 by PI3K signaling has been described in a study of Martínez and colleagues [ 45 ]. They demonstrated that PI3K/AKT activation upregulated Cx50 GJ conductance whereas inhibition of PI3K or AKT decreased Cx50 mediated GJ conductance [ 45 ].…”
Section: Regulation Of Gjs and Hcs By Phosphorylationmentioning
confidence: 98%
“…The interaction of Skp2 with Cx50 at the plasma membrane is thought to mask the nuclear localization signal of Skp2, blocking nuclear translocation and leading to the stabilization of p27 kip1 and p57 kip2 . The PI3K pathway has been implicated in Cx50 regulation, with increased PI3K signaling leading to specific increases in Cx50-mediated coupling (Martinez et al, 2015). Similarly, lens specific knockout of p110α (the catalytic subunit of PI3K) leads to a reduction in cell-cell coupling, reduced proliferation and a microphakic phenotype similar to that seen in Gja8 -null lenses (Sellitto et al, 2016).…”
Section: Molecular Genetic Insights Into Lens Growth Regulationmentioning
confidence: 99%